Antidiabetic and antihyperlipidemic effects of the flower extract of Eriobotrya japonica in streptozotocin-induced diabetic mice and the potential bioactive constituents in vitro. (October 2018) - Lin, Cheng-Hsiu; Shih, Zhao-Zhang; Kuo, Yueh-Hsiung; Huang, Guan-Jhong; Tu, Ping-Chen; Shih, Chun-Ching
Graphical abstract: Highlights: JJ exhibited a significant decrease in the level of blood glucose, triglycerides, and total cholesterol in STZ-induced diabetic mice. JJ notably elevated the expression levels of p-Akt/t-Akt and p-AMPK/t-AMPK in skeletal muscles, implying that the glucose-lowering effects of JJ may act through two pathways involvement in the insulin-Akt or/and AMPK activation. A planation for JJ's anti-diabetic and hypolipidemic activity is that tormentic acid plays the maximum amount of JJ. Abstract: This study was designed to evaluate the effects of flower extracts of Eriobotrya japonica (EJ) on diabetes and hyperlipidemia for 4 weeks in streptozotocin (STZ)-induced diabetic mice. EJ treatment significantly lowered levels of blood glucose, HbA1C, plasma triglyceride (TG), and total cholesterol (TC) but increased the size of the islets of Langerhans within the pancreas. Membrane expression levels of glucose transporter 4 (GLUT4) and phospho-Akt in the skeletal muscles from EJ-treated STZ mice were increased, but G6Pase mRNA levels were decreased, contributing to EJ's antidiabetic activity. EJ caused an increase in hepatic expression of peroxisome proliferator-activated receptor α (PPARα) but a decrease in lipogenic FAS and mRNA levels of SREBP2, which decreased plasma TG and TC levels. One explanation for EJ's antidiabetic and hypolipidemic activity is that tormentic acid represents the major component of EJ. These findings support the amelioration of the diabetic and dyslipidemic state by EJ in STZ-induced diabetic mice.